2012
DOI: 10.1586/erv.12.108
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent Ann Arbor strain live-attenuated influenza vaccine

Abstract: Influenza B is responsible for significant morbidity in children and adults worldwide. For more than 25 years, two antigenically distinct lineages of influenza B viruses, B/Yamagata and B/Victoria, have cocirculated globally. Current influenza vaccine formulations are trivalent and contain two influenza subtype A strains (A/H1N1 and A/H3N2) but only one B strain. In a half of recent influenza seasons, the predominant circulating influenza B lineage was different from that contained in trivalent influenza vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 56 publications
1
18
0
1
Order By: Relevance
“…Clinical trials of the safety and immunogenicity of the different types of TIVs (vs QIVs [30][31][32][33][34]) and LAIVs (vs Q/LAIVs [35,36]) have demonstrated the safety and noninferior immunogenicity of quadrivalent vaccines. Indeed, several trials have shown superior immune responses for the B lineage in the quadrivalent vaccines but not contained in the trivalent vaccines [31,32,[34][35][36].…”
Section: Abstract: Cost-effectiveness • Disease Impact • Economic Evamentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials of the safety and immunogenicity of the different types of TIVs (vs QIVs [30][31][32][33][34]) and LAIVs (vs Q/LAIVs [35,36]) have demonstrated the safety and noninferior immunogenicity of quadrivalent vaccines. Indeed, several trials have shown superior immune responses for the B lineage in the quadrivalent vaccines but not contained in the trivalent vaccines [31,32,[34][35][36].…”
Section: Abstract: Cost-effectiveness • Disease Impact • Economic Evamentioning
confidence: 99%
“…Finally, it is worth noting that only clinical immunogenicity studies have been completed to date on quadrivalent vaccines [31][32][33][34]36]; therefore, assumptions about VE against disease outcomes must be drawn from studies on trivalent vaccines.…”
Section: Measuring the Vaccine Impactmentioning
confidence: 99%
“…Third, recognition that the single B strain hitherto included in trivalent vaccines has resulted in frequent B mismatch in the context of emergence of two distinct B lineage viruses worldwide over several years has resulted in the development of inactivated and live quadrivalent vaccines containing two A and two B strains. Such vaccines will be available in the USA in 2013 and should reach Europe in 2014 25. Finally, efforts are in progress to identify and develop effective vaccines using antigens or epitopes not subject to continuous genetic change, which is such a problem with current vaccines 26.…”
Section: Former Strategies and New Developmentsmentioning
confidence: 99%
“…Part of the determination of vaccine composition involves predicting which one of the two influenza B lineages will be the predominant circulating strain going forward in time and therefore should be included in the vaccine, because immunity to an influenza B strain of one lineage does not confer protection to the alternate lineage. 8,[10][11][12] It is important to note that only 50% of seasonal influenza vaccines between the 2001-2002 and the 2010-2011 influenza seasons contained the vaccine B strain lineage that matched the predominate circulating influenza B virus for that season. This frequent mismatch between vaccine strains and circulating influenza B viruses results in reduced vaccine efficacy and ultimately reduced community confidence in the influenza vaccine.…”
mentioning
confidence: 99%
“…Model analyses indicate that, depending on adequate vaccine supply, burden of influenza, and proportion of influenza B virus contributing to that burden annually, the introduction of quadrivalent influenza vaccine could result in improvement in influenza-associated outcomes. 3,12,13 Specifically, Reed and colleagues showed that the use of a quadrivalent influenza vaccine in the United States during influenza seasons between 2001 and 2008 would have resulted in ~2.7 million fewer cases of influenza, ~21 000 few hospitalizations, and ~1300 fewer deaths. 13 The use of quadrivalent influenza vaccine should reduce mismatch between vaccine and circulating influenza strains and as a result, strengthen the community's confidence in the annual influenza vaccine.…”
mentioning
confidence: 99%